Nonneutral Weibel model plasma in the non-minimal CPT-odd coupling - Soares, D. N.; Belich, H.; Spalenza, W.; Braga, F. L. (The European physical journal. C, Particles and fields, 2024)
Inspired by the extension of the Standard Model, we investigate the effects of the space-time anisotropy caused by Lorentz symmetry violation (LSV) on a plasma column confinement configuration. The model of Plasma taken into account is the z-pinch model that was in the earliest efforts in fusion power research. This model comprises particles in a nonequilibrium cylindrical distribution, which remains stationary in the absence of collisions. We propose a disturbance in the distribution by a Lorentz violation environment. As proposed by Carroll, Field, and Jackiw, in a scenario of (LSV), a background field vector could couple with the electromagnetic field, modifying the classical behavior of the electromagnetic field. As reported here, considering the presence of a background field vector, the intensities of the fields and particle densities would be disturbed by the influence of the LSV. For different values of the background field vector coupling constant, the contribution of the background vector field could modify the intensity of the electromagnetic fields, and concentrate even more the electrons densities in the edge of the plasma column, evidencing a behavior similar to a skin effect in this plasma column.